Ethical Issues in Home Health Care - Smith, Sheri (Charles C Thomas, 2008)
This book will help to answer some of the growing number of ethical questions and more complex issues that home health care nurses face. The cases presented in each chapter of the book are fictionalized situations based on interviews conducted with home health care nurses in both hospital-sponsored and private agencies, in hospices, and in urban and rural settings. Each chapter of the book is devoted to one of the main areas of concern for home health care nurses. Focusing on specific cases, it offers analysis and discussion of the ethical issues, cites legal requirements where relevant, and s